An Analysis of the Repertoire Performed by Youth Orchestras in the United States. Issue 1 (July 2019) - Pope, David A.
The purpose of this study was to develop a deeper understanding of repertoire performed by youth orchestras in the United States. Through an online survey, youth orchestra administrators ( N = 39) provided information about repertoire performed by their program's premier orchestra during their 2015-2016 season. Orchestras performed 302 different pieces of music by 158 different composers. The Firebird by Igor Stravinsky, Carmen Suite No. 1 by Georges Bizet, and Ruslan and Ludmilla Overture by Mikhail Glinka were performed most frequently. Approximately three quarters of all compositions were written after 1850, and only 7.14% were composed after 2000. Compositions by Tchaikovsky, Dvorak, and Brahms were the most frequently performed, and female composers only wrote 0.78% of the repertoire performed by youth orchestras during their 2015-2016 season. Conductors should use these findings as an impetus to identify culturally diverse repertoire appropriate for youth orchestras by non-male composers.